Optimizing Digital HR to Improve Employee Work-Life Balance and Productivity - Yatminiwati, Mimin; Hidayat, Zainul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Digital transformation in the workplace has changed the way companies manage human resources. Amidst the demands of flexible work and operational efficiency, Digital HR (technology-based Human Resource) has become a strategic necessity. The urgency of this research lies in the need to adapt digital technology to support work-life balance and drive employee productivity. Many companies implement flexible work systems, but have not yet fully integrated Digital HR into their HR management processes. The purpose of this research is to analyze the extent to which Digital HR optimization contributes to improving employee work-life balance and productivity. This research also aims to identify the mediating role of work-life balance in the relationship between Digital HR and productivity. Using a descriptive qualitative approach, researchers will explore relevant scientific literature, journals, and prior research. The focus is on identifying patterns, relationships, and best practices in the implementation of Digital HR in various organizations. The results of this research show that the use of digital technology in HR management can help employees better manage their work time and personal lives, thereby improving work-life balance and employee productivity.